Comparison of in vitro velocity measurements in a scaled total cavopulmonary connection with computational predictions - Khunatorn Y. (2014)
A comparison study of in vitro velocity measurements in a scaled total cavopulmonary connection with computational predictions was presented. It was found that the computational fluid dynamics (CFD) model did not reproduce the 3D complexity of flow interactions in the no-offset model with 50:50 flow ratio. The in vitro results showed consistently higher secondary flow components within the pulmonary artery segments, especially for the no-offset model.